The Role of the Organization of Islamic Cooperation Multilateral Diplomacy in Realizing the 2023 Riyadh Summit Mandate for Gaza - Aziz, Azam Azzinnudin; Hidayatullah, Nur Luthfi (Department of International Relations, Universitas Brawijaya, 2026)
This study examines how the Organization of Islamic Cooperation’s Arab–Islamic Ministerial Committee conducted multilateral diplomacy to implement the mandate of the Extraordinary Riyadh Summit in advocating an end to the war on Gaza in 2023. The Committee was established to carry out high-level diplomatic engagements with permanent members of the United Nations Security Council, including China, Russia, the United Kingdom, France, and the United States, to convey collective demands for a ceasefire, expanded humanitarian access, and the enforcement of International Humanitarian Law. Employing a qualitative descriptive approach, the study relies on documentation from official statements, joint communiqués, and international media reports related to these diplomatic visits. The analysis is guided by three key concepts: the role of international organizations, multilateral diplomacy, and mandate implementation, which are used to assess external responses and political support for the Committee's agenda. The findings illustrate that the Committee functioned as a diplomatic actor by coordinating unified messages, enhancing the legitimacy of humanitarian norms, and generating political pressure through multilateral channels. Overall, this study contributes to highlighting the role of non-Western international organizations in shaping diplomatic efforts towards conflict resolution.